Phase analysis of the first pass radionuclide angiocardiogram. Issue 5 (November 1982) - Walton, S; Ell, P J; Jarritt, P H; Swanton, R H
Abstract : Fifty-two subjects with suspected coronary artery disease were studied by first pass radionuclide angiocardiography using a single crystal gamma camera. Phase analysis, a new technique which can detect ventricular regions with abnormal emptying patterns, was applied to the resulting left ventricular radionuclide angiocardiograms. Eighteen turned out be normal and in these subjects the variation of phase values in each of eight ventricular segments was established. Thirty-four had coronary artery disease. By comparison with the normal subjects, 21 had at least one segment with an abnormally high phase value. Such high values were associated with low values of ejection fraction, as determined by a radionuclide technique, total occlusion of a major coronary artery and significant wall motion abnormalities on the radiographic ventriculogram. A comparison between phase analysis and wall motion on a regional basis disclosed progressively high phase values with increasing severity of wall motion abnormality. Particularly high values were found in association with ventricular aneurysm. Phase analysis of first pass radionuclide angiocardiograms is a valid method for the detection of regional abnormalities of ventricular contraction in coronary artery disease.